2006
DOI: 10.1111/j.1365-2591.2006.01065.x
|View full text |Cite
|
Sign up to set email alerts
|

Failure mechanism of ProTaper Ni–Ti rotary instruments during clinical use: fractographic analysis

Abstract: The results suggest that a single overloading event causing ductile fracture of ProTaper instruments is the most common fracture mechanism encountered under the clinical conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
1
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 22 publications
3
51
1
4
Order By: Relevance
“…In the S1 file the SEM photomicrographs showed that fatigue cracks in this file were present after the first use. The fractures found in this present work were due to fatigue, this type of fracture in ProTaper ins-truments has also been described by SpanakiVoreadi et al (19), Peng et al (11) and Wei et al (14) , although the latter also found torsion fractures. Peng et al (11) reported a similar fracture percentage (24.6%) to the one observed here in S1 files.…”
Section: Discussionsupporting
confidence: 87%
“…In the S1 file the SEM photomicrographs showed that fatigue cracks in this file were present after the first use. The fractures found in this present work were due to fatigue, this type of fracture in ProTaper ins-truments has also been described by SpanakiVoreadi et al (19), Peng et al (11) and Wei et al (14) , although the latter also found torsion fractures. Peng et al (11) reported a similar fracture percentage (24.6%) to the one observed here in S1 files.…”
Section: Discussionsupporting
confidence: 87%
“…Two mechanisms that may lead to NiTi rotary fracture, namely cyclic fatigue and torsional overloading, have been described (2,13,(49)(50)(51). Cyclic fatigue occurs as a result of rotation around a curve by repeated extension and compression of the metal and, finally, work hardening followed by fracture (15,49).…”
Section: Mechanical Performance Of Thermomechanically-treated Niti Inmentioning
confidence: 99%
“…However, single-use instruments are used in one tooth, even if the tooth has three or four root canals, as in the case of molars, and are suitable for curved and atretic canals (12). Studies suggest that a disadvantage of single-use instruments is excessive tensile and compression forces on the instrument, which occur with instruments in continuous rotary systems and can cause fracture (13,14).…”
Section: Introductionmentioning
confidence: 99%